2015
DOI: 10.1002/14651858.cd007271.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late tracheostomy for critically ill patients

Abstract: The whole findings of this systematic review are no more than suggestive of the superiority of early over late tracheostomy because no information of high quality is available for specific subgroups with particular characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
275
4
20

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(313 citation statements)
references
References 82 publications
14
275
4
20
Order By: Relevance
“…Compared to LT or prolonged MV, they did not find significantly difference of ET in terms of short-term mortality [relative risk (RR) = 0.91; 95% confidence intervals (cIs) = 0.81−1.03; P = 0.14] or long-term mortality VAP or duration of MV. This result differs from a recent Cochrane Collaboration review that involved seven randomized controlled trials including 1903 participants where the authors found lower mortality rates in the ET as compared with the LT group (risk ratio=0.83; 95% CI 0.70 to 0.98, P = 0.03) [13].…”
Section: Discussioncontrasting
confidence: 99%
“…Compared to LT or prolonged MV, they did not find significantly difference of ET in terms of short-term mortality [relative risk (RR) = 0.91; 95% confidence intervals (cIs) = 0.81−1.03; P = 0.14] or long-term mortality VAP or duration of MV. This result differs from a recent Cochrane Collaboration review that involved seven randomized controlled trials including 1903 participants where the authors found lower mortality rates in the ET as compared with the LT group (risk ratio=0.83; 95% CI 0.70 to 0.98, P = 0.03) [13].…”
Section: Discussioncontrasting
confidence: 99%
“…Although, two more recent analyses suggest superiority of early tracheostomy (43,44), the timing of tracheostomy is dependent mostly on individual and institutional practice.…”
Section: Timing Of Tracheostomymentioning
confidence: 99%
“…We identified one systematic review from Cochrane database which focused on the timing of tracheostomy in the critically ill (56).…”
Section: Resultsmentioning
confidence: 99%